Walking: A Quiet Participation in Place - Markle, Josh; Pelech, Sharon (Journal of the Canadian Association for Curriculum Studies, 2021)
We reflect on experiences we have had working, living and walking alongside our students. We interpret these experiences to reveal the silences at play as we walk stories into being together and attune ourselves to the places we both create and inhabit. We ground our exploration of the connection between walking and curriculum in life writing and literary métissage (Hasebe-Ludt et al., 2009). Throughout, we draw inspiration from Abram (1996) to explore the notion of walking as quiet participation, which we characterize as a bodily attunement toward each other and the more-than-human world, and we point to its possibilities for how we work and live alongside one another.